PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS TI MENGGUNAKAN CANVA BAGI GURU DI SMA PGRI BLAHBATUH PLUS PARIWISATA (PARISMA) - Luh Putu Risma Noviana Risma; Ida Ayu Putu Febri Imawati Febri (Sewagati, 2023)
Canva is a design application that uses drag and drop techniques and can access several existing features such as fonts, images and shapes during the process of making learning media with the rapid development of technology, there is a need for training at SMA PGRI Blahbatuh Plus Pariwista (Parisma) because there are still many educators who have not maximized in mastering the use of Canva as a means of making learning media.